Effects of Complement C4 Gene Copy Number Variations, Size Dichotomy, and C4A Deficiency on Genetic Risk and Clinical Presentation of Systemic Lupus Erythematosus in East Asian Populations - Yih Chen, Ji; Ling Wu, Yee; Yin Mok, Mo; Jan Wu, Yeong‐Jian; Lintner, Katherine E.; Wang, Chin‐Man; Chung, Erwin K.; Yang, Yan; Zhou, Bi; Wang, Huanyu; Yu, Denise J. H. C.; Alhomosh, Alaaedin; et al. (Arthritis & rheumatology (Hoboken, N.J.), 2016)
Objective Human complement C4 is complex, with multiple layers of diversity. The aims of this study were to elucidate the copy number variations (CNVs) of C4A and C4B in relation to disease risk in systemic lupus erythematosus (SLE), and to compare the basis of race‐specific C4A deficiency between East Asians and individuals of European descent. Methods The East Asian study population included 999 SLE patients and 1,347 healthy subjects. Variations in gene copy numbers (GCNs) of total C4, C4A, and C4B, as well as C4‐Long and C4‐Short genes, were determined and validated using independent genotyping technologies. Genomic regions with C4B96 were investigated to determine the basis of the most basic C4B protein occurring concurrently with C4A deficiency. Results In East Asians, high GCNs of total C4 and C4A were strongly protective against SLE, whereas low and medium GCNs of total C4 and C4A, and the absence of C4‐Short genes, were risk factors for SLE. Homozygous C4A deficiency was infrequent in East Asian subjects, but had an odds ratio (OR) of 12.4 (P = 0.0015) for SLE disease susceptibility. Low serum complement levels were strongly associated with low GCNs of total C4 (OR 3.19, P = 7.3 × 10−7) and C4B (OR 2.53, P = 2.5 × 10−5). Patients with low serum complement levels had high frequencies of anti–double‐stranded DNA antibodies (OR 4.96, P = 9.7 × 10−17), hemolytic anemia (OR 3.89, P = 3.6 × 10−10), and renal disease (OR 2.18, P = 8.5 × 10−6). The monomodular‐Short haplotype found to be prevalent in European Americans with C4A deficiency, which was in linkage disequilibrium with HLA–DRB1*0301, was scarce in East Asians. Instead, most East Asian subjects with C4A deficiency were found to have a recombinant haplotype with bimodular C4‐Long and C4‐Short genes, encoding C4B1 and C4B96, which was linked to HLA–DRB1*1501. DNA sequencing revealed an E920K polymorphism in C4B96. Conclusion C4 CNVs and deficiency of C4A both play an important role in the risk and manifestations of SLE in East Asian and European populations.